2023
DOI: 10.1093/rheumatology/kead230
|View full text |Cite
|
Sign up to set email alerts
|

EPCR deficiency ameliorates inflammatory arthritis in mice by suppressing the activation and migration of T cells and dendritic cells

Abstract: Objectives Endothelial protein C receptor (EPCR) is highly expressed in synovial tissues of patients with rheumatoid arthritis (RA), but the function of this receptor remains unknown in RA. This study investigated the effect of EPCR on the onset and development of inflammatory arthritis and its underlying mechanisms. Methods Collagen-induced arthritis (CIA) was induced in EPCR gene knockout (KO) and matched wild type (WT) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This may lead to an increase in pathogenic Th17 cell differentiation in RA patients [146]. Contrarily, mice with severe EPCR deficiency displayed more than 40% reduced arthritis incidence and 50% decreased disease severity when compared to normal mice [147].…”
Section: Epcr and Ramentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to an increase in pathogenic Th17 cell differentiation in RA patients [146]. Contrarily, mice with severe EPCR deficiency displayed more than 40% reduced arthritis incidence and 50% decreased disease severity when compared to normal mice [147].…”
Section: Epcr and Ramentioning
confidence: 99%
“…The same mechanism may apply to RA, although there is no confirmation yet. However, studies have shown that mice with severe EPCR deficiency had a much lower disease incidence and milder arthritis [147], indicating that EPCR could also be a potential therapeutic target for RA. Therefore, it is essential to validate these findings in large clinical cohorts to assess EPCR function and its potential as a therapeutic target for rheumatoid diseases.…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 99%